Ribosomes exist in large excess over the apparent demand for protein synthesis during carbon starvation in marine Vibrio sp. strain CCUG 15956 - Flardh, K.; Cohen, P. S.; Kjelleberg, S. (Journal of Bacteriology, 1992)
Carbon starvation induces the development of a starvation- and stress- resistant cell state in marine Vibrio sp. strain S14 (CCUG 15956). The starved cells remain highly responsive to nutrients during prolonged starvation and exhibit instantaneous severalfold increases in the rates of protein synthesis and RNA synthesis when substrate is added. In order to elucidate the physiological basis for the survival of cells that are starved for a long time, as well as the capacity of these cells for rapid and efficient recovery, we analyzed the ribosome content of carbon-starved Vibrio sp. strain S14 cells. By using direct chemical measurements of the amounts of ribosomal particles in carbon-starved cultures, we demonstrated that ribosomes were lost relatively slowly (half life, 79 h) and that they existed in large excess over the apparent demand for protein synthesis. After 24 h of starvation the total rate of protein synthesis was 2.3% of the rate during growth, and after 3 days this rate was 0.7% of the rate during growth; the relative amounts of ribosomal particles at these times were 81 and 52%, respectively. The ribosome population consisted of 90% 70S monoribosomes, and no polyribosomes were detected in the starved cells. The 70S monoribosomes were responsible for the bulk of the protein synthesis during carbon starvation; some activity was also detected in the polyribosome size region on sucrose density gradients. We suggest that nongrowing carbon-starved Vibrio sp. strain S14 cells possess an excess protein synthesis capacity, which may be essential for their ability to immediately initiate an upshift program when substrate is added.